A comparative study of norethisterone and dydrogesterone in the treatment of heavy menstrual bleeding - Nilofer; M., Narayanaswamy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: HMB is described as bleeding for >7 days or >80 ml per cycle/ having a higher than 100 score on the pictorial blood assessment chart (PBAC). Medical management is the first line of treatment. Norethisterone is most commonly used oral progestin. Dydrogestrone is a C-21 derivative which is highly selective synthetic progestin, closely related to endogenous progesterone. Methods: The 170 cases of heavy menstrual bleeding (HMB) with ovulatory disorder in the range of 20-45 years of age were assigned into two groups (85 women in each group). Group A received Norethisterone 10 mg and Group B received Dydrogesterone 10 mg twice daily respectively till bleeding stopped, the same dose was continued for another one week and then 10 mg OD for one week till 28 days of LMP whichever was later. Both the groups were followed up for another 3 cycles and response to treatment were analysed using PBAC score and Hb levels before and after treatment. Results: A significant decrease in PBAC score and improvement in haemoglobin level were observed in both the groups i.e. 82.35% women in Norethisterone group and 78.82% in Dydrogesterone group respectively. In Norethisterone group 3.53% and 7.08% women in Dydrogesterone group underwent hysterectomy whereas 5.9% women in Norethisterone and 4.7% in Dydrogesterone group opted for therapeutic dilatation and curettage respectively. Conclusions: Dydrogesterone is as effective as Norethisterone in controlling heavy menstrual bleeding. Dydrogesterone can be considered as a safer and efficacious alternative to Norethisterone given its highly selective nature and the absence of androgenic side effects.